APPLICATION OF LINELESS TECHNOLOGY IN AUTOMATIC MOORING USING VACUUM SYSTEM - Kuscahyo, Adhitya Rahman; Buana, I G. N. Sumanta (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2023)
The paper explores the innovative application of lineless technology in automatic mooring systems through the utilization of vacuum systems. Departing from traditional mooring methods, this approach offers enhanced safety, efficiency, and environmental sustainability. The study provides a concise overview of vacuum-based lineless technology's integration in automatic mooring, emphasizing its unique advantages and potential challenges. Vacuum-based lineless mooring systems employ advanced suction mechanisms, sensors, and control algorithms to achieve secure vessel mooring without manual intervention. This novel approach significantly reduces operational risks, minimizes wear and tear, and optimizes berthing precision. The paper delves into the technical intricacies of sensor integration, real-time monitoring, and adaptive controls, ensuring reliable and safe mooring even under dynamic environmental conditions. The adoption of vacuum-based lineless technology introduces considerations like technological reliability, cyber-physical security, vessel adaptability, and port infrastructure compatibility. Through a blend of literature review and practical insights, the paper evaluates the feasibility and economic implications of this approach, highlighting its potential to revolutionize maritime practices. As the maritime industry seeks forward-looking solutions, vacuum-based lineless mooring technology emerges as a promising avenue for reshaping vessel berthing and contributing to sustainable port evolution.